Coding and spacer sequences in the 5.8S-2S region of Sciara coprophila ribosomal DNA. - Jordan, B R (1980)
The sequence of 436 nucleotides around the region coding for 5.8S RNA in the Sciara coprophila rDNA transcription unit (1) has been determined. Regions coding for 5.8S and 2S RNAs have been identified; they are 80 - 90% homologous to the corresponding Drosophila sequences and are separated by a 22 nucleotide long spacer. This sequence as well as the two before the 5.8 and after the 2S coding region are very different from the corresponding Drosophila sequences. The main features reported in the Drosophila study (2) are however also found, i.e. all three spacers are very rich in A-T; the sequence of the internal spacer allows base pairing; 5.8S and 2S RNAs can pair through their 3' and 5' terminal regions respectively. The features previously proposed as processing sites in the Drosophila case are thus all found in Sciara in spite of very different spacer sequences.